AMD RYZEN - Maniyar, Zaheer; Khan, Areeba; Khan, Muzammil; Khan, Samad; Kolad, Ubaid; Kaderiya, Mustaqim (International Journal of Computer Sciences and Engineering, 2019)
In the last few years, technology, especially microprocessors, have had huge advancements and they are expected to have even more in future therefore with this rapidly growing phase of technology, is it still possible to use microprocessors that were considered to be the most advance, at the time, not to long ago? The project aims to analyse the working and applications of the AMD RYZEN microprocessor that was released in 2017. And this analysis in turn will help us to study the latest released microprocessor.